Análises comparativas citogenética e do DNA mitocondrial em Parauchenipterus galeatus Bleeker, 1862, (Siluriformes, Auchenipteridae) coletados no Alto rio Paraná, no Alto rio São Francisco e no rio Piumhi : um enfoque biogeográfico - Lui, Roberto Laridondo (2010)
The Brazilian freshwater ichithyofauna corresponds nearly 55% of species at Neotropical zone, including about 2.500 species grouped in 39 families and belonging to nine orders. Auchenipteridae comprises 20 genera and 90 species. Parauchenipterus presents a widely distribution, occurring across South América, appearing at Paraná- Paraguai, Amazônia, Orenoco Guianas and São Francisco basin, and Brazil´s East. Parauchenipterus galeatus occurs in different Brazilian basins, as Amazon, Prata and São Francisco. The present study describes through basic and molecular cytogenetic, and the sequence of mitochondrial DNA control region, three populations of Parauchenipterus galeatus from Paraná and São Francisco basin, and a probable natural (Wetland of Cururu) and artificial (Piumhi river transposition) connections between this two basins. The diploid number was equal to 58 chromosomes for the three populations; however, variations at the karyotype formula where detected (São Francisco, 22m+16sm+12st+8a; Piumhi, 20m+16sm+14st+8a; Paraná, 24m+18sm+8st+8a). At São Francisco population supernumerary chromosomes where detected. These Bchromosomes are small, metacentric, totally heterochromatics and have numeric variation intra and interindividual. The heterochromatin is located in terminal position from almost all chromosomes, and some metacentric, submetacentric, and subtelocentric chromosomes presents bitelomeric marks, and small pericentromeric blocks in some acrocentric chromosomes, occurring at the three populations. Ag-NORs presented simple at the short arm in an acrocentric pair from all populations, changing only the pair containing this site. In situ hybridization with rDNA 18S probes confirm the chromosome pair evidenced by Ag-NOR in all three populations. The rDNA 5S sites are interstitials, located in two submetacentric chromosome pairs, occurring at short/long arms in all three populations, changing only the pair containing this site. A 847 base pair fragment was amplified through D-loop sequence region from mitochondrial DNA in the three populations, presenting 65 polymorphic sites. The chromosome markers (classic and molecular) and mitochondrial DNA control region analysis shown that Piumhi river population probably already exists at this basin before the transposition. This proposing is based at the chromosome differences between those populations from different basins and mitochondrial DNA sequences, besides the detection of exclusive haplotypes of D-loop from each populations. The control sequences of DNA mitochondrial indicates a strong populational structuring, due to the fixation of molecular table of contents calculated and the fact that each population presents exclusive haplotypes, wich suggests the absence of genic flood among them. However, the chromosome differences show a bigger similarity between São Francisco and Piumhi than Paraná river population. The genetic distance detected among this population trhough the mitochondrial DNA sequences reinforces this nearness between São Francisco and Piumhi. This indicates that possibly this population diverge more recently when compared to Paraná river. The population located on the transposition region presented just one haplotype detected, which indicates the absence of genetic diversity. The present study suggests that, this low diversity is current of a possible population bottle neck with posterior effective size reducing of a population that probably habitats an old wetland (of Cururu) presents at this tansposition region. At the present study, the classic and molecular chromosome markers, allied to the natural basin formation historic context, ecological species aspects, geographic isolation between the basins and into the same basin were used to discuss the biogeographical possible relationship among the Parauchenipterus galeatus populations from different locations.